Retinoid X receptor α and retinoids are key regulators in apoptosis of trophoblasts of patients with recurrent miscarriages - Vattai, Aurelia; Toth, Bettina; Kuhn, C.; Hofmann, S.; Wiest, I.; Wypior, G.; Friese, K.; Jeschke, U. (Journal of molecular endocrinology, 2011)
The retinoid X receptor α (RXRα) is a nuclear hormone receptor that is able to bind other nuclear receptors in a heterodimeric complex, thereby activating gene transcription. Recently, we identified enhanced expression of RXRα in extravillous trophoblasts (EVT) and villous trophoblasts (VT) of miscarried placentas. In addition, an increased number of apoptotic EVT was present in miscarried placentas. In this study, on the basis of immunocytochemical analysis, western blots, and quantitative real-time reverse transcription PCR, we could demonstrate a reduced expression of RXRα in choriocarcinoma cell lines and in human VTs after stimulation with the retinoids 9-cis-retinoic acid and all-trans-retinoic acid and the prostaglandin 15-deoxy-Δ(12,14)-prostaglandin J(2). Furthermore, a simultaneous expression of RXRα and the apoptotic marker M30 CytoDEATH in EVT of miscarried placentas from the first trimester was shown. In EVT of control placentas from legal termination of pregnancies, no co-expression of RXRα and M30 could be detected. A likely conclusion is that RXRα plays an important role in the induction of apoptosis. Downregulation of RXRα, as observed in the tested choriocarcinoma cells and trophoblasts, might serve as a protection against apoptosis and miscarriage. In conclusion, RXRα represents a potential target in the treatment of recurrent miscarriages.
Gesehen am 25.10.2022